A review and evaluation of approaches to measure equity in educational outcomes. Issue 2 (2nd April 2020) - Nachbauer, Max; Kyriakides, Leonidas
ABSTRACT: This paper provides a critical review of indicators that can be used to measure equity in educational outcomes. These indicators are evaluated using different criteria. Further, analysis on how the sample structure affects equity measurements is undertaken. Analyses are based on theoretical reasoning and empirical data from the German National Educational Panel Study. This study is focused on achievement gaps related to socioeconomic status within secondary school classes. Results suggest medium to high convergent validity between different indicators. Longitudinal indicators outperform cross-sectional indicators in regard to considering student intake. Multilevel indicators are advantageous for handling sampling error. However, indicators based on ordinary least squares regression analysis and mean differences can be standardised and are easy to interpret. A strategy for choosing appropriate indicators to measure equity in education is presented. In regard to the sample structure, the number of students per class was found to be crucial for equity measurements.